The bony labyrinth of the middle Pleistocene Sima de los Huesos hominins (Sierra de Atapuerca, Spain). Issue 90 (January 2016) - Quam, Rolf; Lorenzo, Carlos; Martínez, Ignacio; Gracia-Téllez, Ana; Arsuaga, Juan Luis
Abstract: We performed 3D virtual reconstructions based on CT scans to study the bony labyrinth morphology in 14 individuals from the large middle Pleistocene hominin sample from the site of the Sima de los Huesos (SH) in the Sierra de Atapuerca in northern Spain. The Atapuerca (SH) hominins represent early members of the Neandertal clade and provide an opportunity to compare the data with the later in time Neandertals, as well as Pleistocene and recent humans more broadly. The Atapuerca (SH) hominins do not differ from the Neandertals in any of the variables related to the absolute and relative sizes and shape of the semicircular canals. Indeed, the entire Neandertal clade seems to be characterized by a derived pattern of canal proportions, including a relatively small posterior canal and a relatively large lateral canal. In contrast, one of the most distinctive features observed in Neandertals, the low placement of the posterior canal (i.e., high sagittal labyrinthine index), is generally not present in the Atapuerca (SH) hominins. This low placement is considered a derived feature in Neandertals and is correlated with a more vertical orientation of the ampullar line (LSCm < APA), posterior surface of the petrous pyramid (LSCm > PPp), and third part of the facial canal (LSCm < FC3). Some variation is present within the Atapuerca (SH) sample, however, with a few individuals approaching the Neandertal condition more closely. In addition, the cochlear shape index in the Atapuerca (SH) hominins is low, indicating a reduction in the height of the cochlea. Although the phylogenetic polarity of this feature is less clear, the low shape index in the Atapuerca (SH) hominins may be a derived feature. Regardless, cochlear height subsequently increased in Neandertals. In contrast to previous suggestions, the expanded data in the present study indicate no difference across the genus Homo in the angle of inclination of the cochlear basal turn (COs < LSCm). Principal components analysis largely confirms these observations. While not fully resolved, the low placement of the posterior canal in Neandertals may be related to some combination of absolutely large brain size, a wide cranial base, and an archaic pattern of brain allometry. This more general explanation would not necessarily follow taxonomic lines, even though this morphology of the bony labyrinth occurs at high frequencies among Neandertals. While a functional interpretation of the relatively small vertical canals in the Neandertal clade remains elusive, the relative proportions of the semicircular canals is one of several derived Neandertal features in the Atapuerca (SH) crania. Examination of additional European middle Pleistocene specimens suggests that the full suite of Neandertal features in the bony labyrinth did not emerge in Europe until perhaps <200 kya.